2022
DOI: 10.3390/su14063469
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as a Key Constituent for Smart Specialization Strategies (S3), What Is in It for Peripheral Regions? Co-creating Sustainable and Resilient Tourism with Cultural and Creative Industries

Abstract: Sustainable tourism is one of the key sectors in the South Baltic Sea Region (SBSR), which belongs to the role model for sustainability—the Baltic Sea Region (BSR). In this context, resilience, recovery and sustainability become key common threads calling for new approaches mitigating negative impacts, upscaling resilience capacity and boosting recovery in the post-pandemic era. The present work aims at revealing conceptual and practical pathways for policy makers and businesses in revitalizing sustainable tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 176 publications
1
6
1
Order By: Relevance
“…Literature and empirical investigation specifically focusing on CCIs and tourism interrelationships within RIS3 is still limited. Indeed, a research gap has been observed about smart specialisation, CCIs and tourism (Biagi et al, 2021;Meyer et al, 2022). At a general level, it has been noted that RIS3 tend to focus on science and high technology-related industries, neglecting industries such as tourism (Weidenfeld, 2018) and CCIs (Stanojev and Gustafsson, 2021;Meyer et al, 2022).…”
Section: The Ccis-tourism Nexus In Smart Specialisation Strategies (R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature and empirical investigation specifically focusing on CCIs and tourism interrelationships within RIS3 is still limited. Indeed, a research gap has been observed about smart specialisation, CCIs and tourism (Biagi et al, 2021;Meyer et al, 2022). At a general level, it has been noted that RIS3 tend to focus on science and high technology-related industries, neglecting industries such as tourism (Weidenfeld, 2018) and CCIs (Stanojev and Gustafsson, 2021;Meyer et al, 2022).…”
Section: The Ccis-tourism Nexus In Smart Specialisation Strategies (R...mentioning
confidence: 99%
“…Indeed, a research gap has been observed about smart specialisation, CCIs and tourism (Biagi et al, 2021;Meyer et al, 2022). At a general level, it has been noted that RIS3 tend to focus on science and high technology-related industries, neglecting industries such as tourism (Weidenfeld, 2018) and CCIs (Stanojev and Gustafsson, 2021;Meyer et al, 2022). This conclusion is supported by the findings of the mapping of innovation priorities between 2014 and 2020 by the Joint Research Centre (Sörvik and Kleibrink, 2015) showing that the most common priority in the main categories of "research and innovation capability" was manufacturing and industry (34.6%), whereas creative and cultural arts and entertainment and tourism, restaurants and recreation only accounted for 4.6% and 3.9%, respectively, of total priorities.…”
Section: The Ccis-tourism Nexus In Smart Specialisation Strategies (R...mentioning
confidence: 99%
“…Finally, opportunities for further research by tourism researchers are presented. This paper presents a critical review of current research and key factors in digital entrepreneurship and the creative industries in tourism (Ngoasong 2018;Meyer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…-shared direction towards the SDGs; -whole-system transformation towards sustainability; -responsibility and reflexivity (Miedzinski et al, 2021).…”
mentioning
confidence: 99%
“…With the accumulation of empirical material, there are surveys dedicated to studying the practice of using Smart Specialisation to achieve Sustainability. In particular, new connections between local assets, potential markets and social problems of regional development are revealed on the basis of S3 (Meyer et al, 2022) and Sustainability in regions is analysed through the implementation of the concept of Smart Specialisation (Šipilova et al, 2017). Special attention in these studies is paid to rural and peripheral regions, which are the most problematic from the point of view of both promoting the ideas of Smart Specialisation and meeting the sustainable development challenges.…”
mentioning
confidence: 99%